Peculiarities of isolation of biologically active substances from St. John's wort (Hypericum perforatum L.) - Poltoratska, Tetiana; Maga, Ivan (Problems of Environmental Biotechnology, 2024)
The peculiarities of the isolation of biologically active substances from St. John's wort (Hypericum perforatum L.) are shown.